Investigating the Macular Vasculature Using Optical Coherence Tomography Angiography Following Pan-Retinal Photocoagulation in Diabetic Retinopathy - Mohammadreza Ansari Astaneh; Nasim Shahsavan Gharbi; Mojtaba Abrishami; Elham Bakhtiari; Mehrdad Motamed Shariati (Frontiers in Biomedical Technologies)
Purpose: This study used Optical Coherence Tomography Angiography (OCTA) to examine the progression of the macular flow profile over the course of a month following Pan-Retinal Photocoagulation (PRP).